Influence of pre-strain on the formability of 2024 aluminium alloy - Bressan J.D.* (2009)
Present work investigates the influence of pre-strain on the limiting strains in sheet metal forming, using the strain gradient evolution model that predict the onset of local necking from initial thickness imperfections, roughness waviness and thickness gauge. The theoretical analysis is compared with the experimental results for fully annealed and three pre-strain levels of 4 %, 8 % and 12 % in 2024 aluminium alloy sheet with thickness of 2.5 mm presented by Leacock et al. at ESAFORM 2008. The effect of strain and strain rate hardening behaviour, pre-strain and anisotropy parameters in material formability are analyzed. The experimental forming limit curves indicate an immediate drop in the limiting strains in the pre-strained specimen when compared with the full annealed condition material as expected from the theoretical prediction by a new model. Other relevant aspects of the new approach to modeling FLC are also discussed. © Springer/ESAFORM 2009.